Implementasi Model Discovery Learning berbantuan PhET Simulations pada Materi Dinamika Gerak dalam Program Kampus Berdampak - Hikmawati Hikmawati; Diah Eka Hapsari; Endah Sunarti (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aimed to describe the implementation of the Discovery Learning model assisted by PhET Interactive Simulations on the topic of dynamics of motion in the School Field Introduction Program as part of the Campus Impact Program. This research employed a quantitative descriptive approach conducted at SMA Negeri 7 Mataram during the odd semester of the 2025/2026 academic year. The research subjects consisted of 36 eleventh-grade students in Phase F. Data were collected through tests and observations. The research instruments included multiple-choice test sheets and observation sheets for students’ attitudes and skills. The data were analyzed using descriptive statistics through mean scores, percentages, and interpretation of learning outcome categories. The results showed that the implementation of the discovery learning model assisted by PhET Interactive Simulations had a positive impact on students’ learning outcomes. In the cognitive aspect, students achieved an average score of 85.38, categorized as very good. In the affective aspect, the average score reached 76.39, categorized as good, as reflected in the development of critical thinking, independence, collaboration, creativity, and noble character. In the psychomotor aspect, students obtained an average score of 80.92, categorized as good, particularly in observing, questioning, predicting, conducting investigations, and communicating results. The findings indicate that the implementation of discovery learning supported by digital simulation media was able to create an active, interactive, and meaningful physics learning environment while representing the practical implementation of the Campus Impact Program in schools.